The Restriction of Some Rights in Romania in the Context of the Covid-19 Pandemic: Array - Vișan, Oana Mihaela (Journal of Danubian Studies and Research, 2020)
When analyzing the exceptions to inalienable nature of human rights, we refer to two categories of rights: absolute rights, which are not to be infringed under any circumstances, and relative rights, the exercise of which may be restricted in certain situations that have been strictly prescribed. The issue that gives rise to legal debates is related to the conditions imposed by Article 53 of the Constitution, which provides that the restriction be prescribed “by law”, be “required in a democratic society” and “proportionate to the situation having caused it.”